The effects of previous educational training on physical activity counselling and exercise prescription practices among physicians across Nova Scotia: a cross-sectional study - O'Brien, Myles; Shields, Chris; Crowell, Sandra; Theou, Olga; McGrath, Patrick; Fowles, Jonathon (Canadian Medical Education Journal, 2018)
Background: Physicians (MDs) report difficulty including physical activity (PA) and exercise (PAE) as part of routine care. MDs who report previous educational training in PAE may prescribe exercise more frequently. We evaluated the effects of previous training on perceptions and practices of PA counselling and exercise prescriptions among MDs in Nova Scotia. Methods: MDs (n=174) across Nova Scotia completed an online self-reflection survey regarding their current PAE practices. MDs who reported previous training (n=41) were compared to those who reported no training (n=133). Results: Trained-MDs were 22% more confident performing PA counselling than untrained-MDs (p<0.005). In patient appointments, trained-MDs included PAE more often (51% vs 39%; p=0.03) but trained-MDs and untrained-MDs had similar rates of exercise prescriptions (12%; p>0.05). The most impactful barriers (on a scale of 1 to 4) were lack of time (2.5) and perceived patient interest (2.4), which were unaffected by previous training (p>0.05). Conclusion: Previous training was associated with a higher confidence to include PAE discussions with patients by MDs in Nova Scotia, but had minimal influence on their many barriers that prevent exercise prescription. Although some training supports MDs inclusion of PAE into their practice, there is a need for greater, more intensive educational training to assist MDs in prescribing exercise.